BIOM-26. SURVIVAL OUTCOMES AND PROGNOSTIC FACTORS IN PRIMARY GLIOBLASTOMA FROM A REAL-WORLD RETROSPECTIVE STUDY. (12th November 2021) - Brown, Nicholas; Ottaviani, Diego; Tazare, John; Gregson, John; Kitchen, Neil; Brandner, Sebastian; Fersht, Naomi; Mulholland, Paul
Abstract: INTRODUCTION: Glioblastoma has limited therapeutic options and is associated with a poor prognosis. Treatment, clinical outcomes, and prognostic factors remain poorly characterised outside of the selected population enrolled in clinical trials. METHODS: Demographic, tumour molecular profiles, treatment, and survival data was collated for patients who underwent a biopsy or resection diagnostic of de novo glioblastoma at our centre between July 2011 and December 2015. We used multivariate proportional hazards models to examine the association of potential prognostic markers with survival. RESULTS: 490 patients were identified: 60% were male with a median age of 59 years. 60% of patients had surgical debulking, and 40% biopsy only. Subsequently, 56% had standard chemoradiotherapy, 25% non-standard chemo/radio-therapy, and 19% no further treatment; 22% of patients who had adjuvant therapy had surgery at relapse, 37% second-line chemotherapy, and 11% third-line chemotherapy. Median survival was 9.2 months (IQR 7.9-10.3 months), with survival at 12- and 24-months 41% and 13% respectively. In multivariate analysis, longer survival was associated with debulking surgery vs biopsy alone (14.9 vs 8 months) (HR 0.54 [95%CI 0.41-0.70]); subsequent treatment after diagnosis (HR 0.12 [0.08-0.16]) (standard chemoradiotherapy [16.9 months] vs non-standard regimens [9.2 months] vs none [2.0 months]); tumour MGMT promotor methylation (HR 0.71 [0.58-0.87]); and younger age (hazard ratio vs age< 50: 1.70 [1.26-2.30] for ages 50-59; 3.53 [2.65-4.70] for ages 60-69; 4.82 [3.54-6.56] for ages 70+). IDH mutation was associated with longer survival (HR 0.64 [0.66-0.97] in univariate but not multivariate analysis. CONCLUSION: Median survival for patients with glioblastoma is less than a year. Younger age, debulking surgery, treatment with chemoradiotherapy, and MGMT promotor methylation are independently associated with longer survival.